Pengembangan Usaha Budidaya Ikan Hias Channa Dalam Meningkatkan Kualitas Javachanna Di Kota Banyuwangi - Mohammad Mirza Pratama; M. Izzul Firmansyah (CV. ITTC INDONESIA, 2025)
This study aims to describe the development of ornamental fish farming business channa in UMKM Java Channa, Banyuwangi. The research method used is qualitative descriptive with data collection through in-depth interviews, participatory observation, and literature review. The results of the study indicate that channa fish farming in UMKM Java Channa has great potential. Various intensive training activities, such as proper feeding, aquarium maintenance, and mental training of fish, are carried out to produce high-quality channa fish. UMKM Java Channa also plays a role in increasing community knowledge and skills in the field of ornamental fish farming. In addition, this study also reveals that channa fish farming can be a promising alternative livelihood, especially for people affected by the Covid-19 pandemic.